Howard Bond: Revealing Moments. - Biggerstaff, Eric (View Camera)
The article features photographer Howard Bond. He began his lifelong passion for photography in 1944, when, in the eight grade, he was given a large roll film camera. he built up a career in fine art photography while studying as a computer programming at the University of Michigan. During the popularity of 35mm cameras, he switched from roll film to 9x12cm sheet film. He became influenced by the members of Group f/64 and embraced their attitude toward sharp, straight photographs. He has had over 60 one-man and 40 two-man shows during his long career.